Characterization of Heat Shock Protein (HSP 70) Sequence in Leishmania donovani - Maharjan, Mahendra (Journal of Institute of Science and Technology, 2015)
Heat shock protein HSP70 is the highly conserved protein along the kinetoplastid phylogenetic spectrum. A full length hsp70 gene was amplified, cloned and sequenced. The protein sequence was aligned and phylogentic tree was constructed. The Leishmania donovani HSP70 protein sequence (653 amino acids) is slightly larger than the Human HSP70 protein sequence (641 amino acids) with 72% identity. The putative protein sequence is 98%, 97%, 96% and 92% identical to L. major, L. infantum, L. tarentolae and L. braziliensis respectively. Evolutionary relationship showed that kinetoplastid parasites are closely related to the human compared to prokaryotes, E. coli. Journal of Institute of Science and Technology, 2015, 20(1): 82-86